2021
DOI: 10.1007/s00268-021-06061-z
|View full text |Cite
|
Sign up to set email alerts
|

Non‐operative Management of Small Bowel Obstruction in Patients with No Previous Abdominal Surgery: A Systematic Review and Meta‐analysis

Abstract: While the contemporary management of adhesive small bowel obstruction (SBO) often includes a trial of non-operative management (NOM), surgical dogma dictates urgent operative exploration in patients without previous abdominal surgery. This dogma has been challenged by recent evidence suggesting most obstructions in this population are adhesive in nature. The objectives of this review were to evaluate the feasibility of NOM in patients with SBO and no history of previous abdominal surgery, to examine the etiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…The scenario becomes more intricate when noting that this failure rate climbs to 50% in patients who did not receive the oral contrast. 22 Furthermore, a recent systematic review, incorporating two cohort studies and four case reports, posited the success rate of conservative management to lie between 50 and 70% for SBO-VA. 23 In comparison to these findings, our research reported a success rate of 90.6% for non-operative strategies in the context of SBO-VA.…”
Section: Discussionmentioning
confidence: 46%
“…The scenario becomes more intricate when noting that this failure rate climbs to 50% in patients who did not receive the oral contrast. 22 Furthermore, a recent systematic review, incorporating two cohort studies and four case reports, posited the success rate of conservative management to lie between 50 and 70% for SBO-VA. 23 In comparison to these findings, our research reported a success rate of 90.6% for non-operative strategies in the context of SBO-VA.…”
Section: Discussionmentioning
confidence: 46%
“…In recent years, there has been a move towards trialling non‐operative management of SBO in the virgin abdomen in well patients. However, failure of non‐operative management and non‐resolving SBO warrants exploratory surgery, and up to 50% of non‐operatively managed SBOs in a virgin abdomen will proceed to surgical intervention 8 …”
Section: Figmentioning
confidence: 99%
“…However, failure of non-operative management and non-resolving SBO warrants exploratory surgery, and up to 50% of non-operatively managed SBOs in a virgin abdomen will proceed to surgical intervention. 8 The diagnosis of CD relies on the combination of clinical findings, radiological evidence, serology and histology. However, with a >90% sensitivity and specificity of MRE in detection of active CD, it is of increasing clinical utility in the diagnosis and management of CD.…”
Section: Claimed 75%mentioning
confidence: 99%
“…The decision-making process surrounding operative versus nonoperative management (NOM) in cases of intestinal obstruction presents a significant challenge in the field of medical practice. 7,8 Despite the wealth of radiological and clinical data available, the distinction between these management approaches remains elusive.…”
Section: Introductionmentioning
confidence: 99%